2019
DOI: 10.5194/tc-13-351-2019
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic preferred orientations of ice deformed in direct-shear experiments at low temperatures

Abstract: Abstract. Synthetic polycrystalline ice was sheared at temperatures of −5, −20 and −30 ∘C, to different shear strains, up to γ=2.6, equivalent to a maximum stretch of 2.94 (final line length is 2.94 times the original length). Cryo-electron backscatter diffraction (EBSD) analysis shows that basal intracrystalline slip planes become preferentially oriented parallel to the shear plane in all experiments, with a primary cluster of crystal c axes (the c axis is perpendicular to the basal plane) perpendicular to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(110 citation statements)
references
References 88 publications
(150 reference statements)
10
69
1
Order By: Relevance
“…1) at all temperatures first rise to the peak stresses and then relax to approach near-constant stresses with strains. This pattern matches published constant-displacement-rate experiments (Mellor and Cole, 1982;Durham et al, 1983;Durham et al, 1992;Piazolo et al, 2013;Vaughan et al, 2017;Qi et al, 2017;Craw et al, 2018;Qi et al, 2019), and is comparable to the constant-load experiments (Budd and Jacka, 1989;Jacka and Li, 2000;Treverrow et al, 2012;Wilson and Peternell, 2012) where strain rate first decreases to a minimum and then increases to approach a near-constant strain rate.…”
Section: Inferences From Mechanical Evolutionsupporting
confidence: 88%
See 3 more Smart Citations
“…1) at all temperatures first rise to the peak stresses and then relax to approach near-constant stresses with strains. This pattern matches published constant-displacement-rate experiments (Mellor and Cole, 1982;Durham et al, 1983;Durham et al, 1992;Piazolo et al, 2013;Vaughan et al, 2017;Qi et al, 2017;Craw et al, 2018;Qi et al, 2019), and is comparable to the constant-load experiments (Budd and Jacka, 1989;Jacka and Li, 2000;Treverrow et al, 2012;Wilson and Peternell, 2012) where strain rate first decreases to a minimum and then increases to approach a near-constant strain rate.…”
Section: Inferences From Mechanical Evolutionsupporting
confidence: 88%
“…3(d For each sample, we calculated the mean grain diameter ( B ), the peak grain diameter ( CDEF ) and square mean root diameter Table 3. While the mean diameter, B , is commonly used for grain size analyses in the literature (e.g., Jacka, 1994;Piazolo et al, 2013;Vaughan et al, 2017;Qi et al, 2017;Qi et al, 2019), Lopez-Sanchez and Llana-Fúnez (2015) showed that the frequency peak ( CDEF ) of a grain size distribution provides the most robust measure of the recrystallized grain size. However, the population of grains smaller than CDEF is too small to provide representative CPO information for most of the data sets in this study.…”
Section: Grain Sizementioning
confidence: 99%
See 2 more Smart Citations
“…M max is the calculated torque, τ max is the maximum calculated shear stress, ε max is the maximum measured strain, andγ f andε f are the final measures shear strain rate and strain rate. ∼ 1 × 2 cm 2 , but is able to recover the full orientation of the crystal (all crystallographic axes) with an expected angular resolution better than 0.7 • (Randle, 1992) and with a practical spatial resolution for ice down to 5 µm. Sections tangential to the experimental cylinders were cut out for both AITA and EBSD analyses.…”
Section: Methodsmentioning
confidence: 99%